Effect of surface morphology of nanostructured rutile TiO2 nanorods/nanoflowers as photoelectrode on the performance of dye-sensitized solar cell - Ahmad, Mohd Khairul (2013)
Aligned Rutile TiO2 nanorods (r-TNRs) and TiO2 nanoflowers (r-TNFs) were successfully prepared by hydrothermal method. Using hydrochloric acid (HCl) as chelating agent and titanium butoxide (TBOT) as precursor, aligned r-TNRs with r-TNFs were successfully growth onto fluorine-doped tin oxide (FTO) with different morphologies. The influences of surface morphologies to the rutile based Dye-sensitized solar cell (DSC) efficiency are discussed. The highest light-to-electric energy conversion efficiency, 1.80% is achieved using different concentration under simulated solar light illumination of 100 mWcm-2 (1.5 AM).